Fitness clubs facing COVID-19 lockdown - Komanda, M. (Humanitas University's Research Papers Management, 2020)
The establishment of the state of epidemic in Poland in March 2020 caused significant difficulties in accessing certain services or a total ban on their rendering. The fitness industry faced the inability to provide activity. This extraordinary situation forced entities in the fitness industry (including fitness clubs) to face a number of challenges related to surviving the closing period. The-se include, first of all, financial issues, the development of electronic business model components, as well as thinking about the conditions of running business after lifting the ban. The aim of the paper is to analyse the actions taken by the Polish fitness clubs during the lockdown period (13/03/2020-06/06/2020) caused by the coronavirus pandemic (COVID-19). It covers recognizing the thinking of these clubs about the possibilities of acting despite these restrictions, as well as immediately after lifting restrictions on the service activities of this industry. The method of analysing the situation of the industry was based on two sources of information: a review of the literature and industry reports on the situation before the lockdown and media information presenting its state during the lockdown. The combination of information from both sources gave a unique insight into the justi-fications of the activities announced and undertaken by the Polish fitness club industriy.